(untitled) (Revista VIS: Revista do Programa de Pós-Graduação em Artes Visuais, 2020)
This article discusses two aspects of O Mez da Grippe, by the Brazilian writer Valêncio Xavier: the graphic composition and the generation of meanings through historical references in the work. In the first part, using Gérard Genette’s concept of paratextuality, we analyze some graphic characteristics of the text that enclose Dona Lúcia’s narrative, a (fictional?) survivor of the Spanish flu. In the second, we seek to demonstrate, in the light of Wolfgang Iser’s concepts of empty spaces or points of indeterminacy, implicit reader, and asymmetry between text and reader, how historical references can contribute to the reader’s response.